Penerapan Model Pembelajaran Berbasis Masalah Berbantuan Pictorial Riddle untuk Meningkatkan Hasil Belajar Kognitif dan Keterampilan Berpikir Kritis Peserta Didik pada Materi Pokok Elastisitas dan Hukum Hooke Kelas XI IPA2 SMA Negeri 1 Loghia - Hasriani, Wa Ode; Anas, Muhammad; Sahara, La (Jurnal Penelitian Pendidikan Fisika, 2020)
This study aims to: 1) describe the improvement of student learning outcomes in learning physics class XI IPA2 SMA Negeri 1 Loghia which is taught by using a problem-based learning model assisted by pictorial riddle on the subject matter of elasticity and hooke law. 2) describe the improvement of students' critical thinking skills in physics learning class XI IPA2 SMA Negeri 1 Loghia on the subject matter of elasticity and hooke law taught by using problem-based learning models assisted by pictorial riddle 3) describe the completeness of students learning in physics learning class XI IPA2 Loghia State High School 1, which is taught by using a pictorial riddle-based problem-based learning model on the subject of elasticity and hooke law. The data analysis was performed by descriptive statistics. From the analysis of the data obtained the average of cognitive learning outcomes of students in the first cycle is 74.71. The average critical thinking skills in the first cycle are indicators giving 38.79 simple explanations, building basic skills 28.45, concluding 38.79, making further explanation 31.90 and indicators of strategy and tactics 50.86. As for the percentage of mastery learning classically in the first cycle of 65.52%. In the second cycle obtained the average of cognitive learning outcomes of 79.83. The average critical thinking skills in the second cycle of the indicators provide a simple explanation of 57.76, building basic skills 84.48, concluding 93.10, making further explanation 74.13 and indicators of strategy and tactics 88.79. While the percentage of mastery learning classical students in the first cycle amounted to 79.31%. Based on the results of the research and discussion it can be concluded that the application of problem based learning model assisted by pictorial riddle can improve cognitive learning outcomes and critical thinking skills.Â